Establishing Land Rights: The Vital Role of Indigenous Community Institutions in Controlling Land Ownership Certificates - Ririhena, Samel W.; Tambajong , Hesty; Oja, Hubertus; Moento, Paul A. (International Journal of Social Science and Business, 2024)
The current issues related to land ownership rights revolve around the frequent complaints from the community about the authenticity of customary land release documents and some individuals within the indigenous community deliberately selling communal land that does not belong to them. Hence, it is necessary to analyze the role of the Indigenous Community Institution (ICI) in addressing land ownership issues. This research is qualitative in nature, with the research subjects being members of the ICI of Village and the indigenous community present in the village. The data collection methods used include observation, interviews, and documentation. After obtaining data through observation, interviews, and document collection, this data will go through a systematic series of analysis stages. These stages include data reduction, data presentation, and drawing conclusions based on information obtained from informants or sources related to the role of the Indigenous Community Institution (ICI) in supporting the issuance of land ownership certificates. The Indigenous Community Institution (ICI) of Village has three main roles, namely the Interpersonal Role, the Informational Role, and the Decision-Making Role. The ICI serves as a bridge between the indigenous community, the government, and the general public, with the aim of ensuring fair and pro-indigenous community policies. To enhance its effectiveness, communication and collaboration between the ICI, the government, and the community need to be strengthened. Additionally, there should be education and awareness-raising among the indigenous community regarding their customary land ownership rights.